Understanding writing teachers’ technological pedagogical content knowledge: A study with five in-service teachers - Cheung, Yin Ling; Jang, Hari (Indonesian Journal of Applied Linguistics, 2020)
The growing emphasis on emerging technologies in education has required in-service teachers to develop more technological knowledge. However, little is known about the application of technological pedagogical content knowledge (TPACK) on subject matter knowledge in language teaching. This qualitative study examined five writing teachers’ implementation of instructional objectives, instructional strategies, and technologies to teach writing as well as their assessment of learning using the TPACK-Writing perspective. Lesson observations were conducted for each teacher. Adopting a case study design, the observation transcripts were analyzed with a focus on the teachers’ execution of the instructional objectives, instructional strategies, and technologies to teach writing as well as their assessment of learning. The results showed that the complex nature of writing pedagogy with TPACK-Writing as a construct was mediated by cultural factors such as an examination-oriented system and teacher-centered pedagogy. The results also suggested that the application of TPACK-Writing should involve a student-centered approach rather than a teacher-centered approach, which implies the need for teachers to acquire a high level of knowledge of learners and the instructional context to promote effective pedagogy.